An update on the genetics of colorectal cancer. - Kemp, Z; Thirlwell, C; Sieber, O; Silver, A; Tomlinson, I (2004)
Colorectal carcinoma (CRC) remains a frequent cause of cancer-associated mortality in the UK and still has a relatively poor outcome. Single gene defects account for up to 2-6% of cases, but twin studies suggest a hereditary component in 35%. CRC represents a paradigm for cancer genetics. Almost all the major-gene influences on CRC have been identified, and the identification of the remaining susceptibility alleles is proving troublesome. Only a few low-penetrance alleles, such as methylene tetrahydrofolate reductase C677T, appear convincingly to be associated with CRC risk. To identify the remaining CRC genes, parallel approaches, including strategies based on linkage and association and complementary analyses such as searches for modifier genes, must be employed. To gain sufficient evidence to prove that a gene is involved in CRC predisposition, it is probably necessary for multiple, adequately-powered studies to demonstrate an association with the disease, especially if the allelic variants have only a small differential effect on risk. It may also be possible to show how genes interact with each other and the environment, although this will be even more difficult. Accurate quantitation of the allele-specific risks in different populations will be necessary, but problematic, especially if those risks combine in a fashion which is not of a straightforward additive or multiplicative type. Without any good prior evidence of the nature of the remaining genetic influence on CRC, the possibility remains that this is a truly polygenic trait or that multiple, rare variants contribute to the increased risk; in these cases, identification of the genes involved will be very difficult. Despite these potential problems, the effectiveness of preventive measures for CRC, especially in high-risk individuals, means that the search for new predisposition genes is justified.